Entrepreneurial strategies for transformative change: An application to grassroots movements for sustainable urban water systems. (15th November 2022) - Pakizer, Katrin; Fischer, Manuel; Lieberherr, Eva
Highlights: Grassroots movements frame, aggregate, mobilize and network to foster innovations. Entrepreneurial strategies are used for investigating grassroots movements' activities. A Swiss case of urban water transition shows how these strategies function together. Grassroots movements choose their strategies depending on the local context. Interaction effects exist between entrepreneurial strategies.